COGNITIVE LINGUISTICS: EXPLORING THE INTERCONNECTION BETWEEN LANGUAGE, COGNITION, AND EXPERIENCE - Zaynieva Gulchaman Ilhomjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. Cognitive linguistics constitutes an interdisciplinary framework that examines language as an integral component of human cognitive functioning rather than as an isolated, innate system. It emphasizes that linguistic meaning arises from conceptual structures shaped by bodily experience, cultural knowledge, and patterns of language use. This article offers a synthesized account of Cognitive linguistics by outlining its theoretical origins, foundational assumptions, methodological orientation, and central domains of inquiry, including conceptualization, metaphor, embodiment, and usage-based grammar. Drawing on influential contributions by Langacker, Lakoff, Talmy, and subsequent scholars, the study demonstrates that meaning construction is dynamic, experience-based, and cognitively motivated. The findings underline the significance of Cognitive linguistics for contemporary linguistic theory and its applications in applied linguistics and cognitive science.